RESPON MASYARAKAT MENGENAI COVID 19 DI KABUPATEN INDRAMAYU JAWA BARAT - Lina Rahmawati; Riyanto Riyanto; Asmadi Asmadi (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
The public's response to the corona virus outbreak has varied, some are following health protocols, but for economic reasons, they have to leave the house and survive. In order for the community to survive this pandemic and apart from the outbreak, we as the Indramayu Regency Disaster Risk Reduction Forum (FPRB)/Forum Pengurangan Resiko Bencana (FPRB)is deemed important to determine the extent of the public's response to the Covid 19 pandemic outbreak. This type of research is descriptive quantitative. Data was obtained from 31 Districts in Indramayu Regency, then the data was analyzed and the data was obtained by the community getting information about the corona virus from electronic television media, the community understood what ODP and PDP were, the community got information about Covid 19 so that they were more careful and vigilant, people reduced their activities in outside the home, make government calls not to visit crowded places such as markets, malls, etc., always wear personal protective equipment such as masks when talking to other people or going out of the house, if there are neighbors or relatives who cough a cold then stay away from not interacting with this person, prevents transmission of the corona virus by getting plenty of rest, eating fruits and vegetables, trying to wash hands more often with soap and hand sanitizer, maintaining a clean and healthy lifestyle, exercising diligently, checking health. It was concluded that currently the corona virus still exists and the sufferers are increasing even though some have recovered. The recommendations from this research are a reference for stakeholders, especially local governments, to reduce and cope with the Covid 19 disaster in Indramayu. The government must collaborate with organizations and communities to participate in efforts to tackle the Covid 19 outbreak, including FPRB which has an important role in disasters.